Die notarielle Urkunde im italienisch-deutschen Vergleich: Überlegungen zur Übersetzung von Immobilienkaufverträgen - Wiesmann, Eva (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2013)
Notarial documents have some translation-relevant particularities which are strongly associated with the legal culture of the respective country. They are subject to competing influential factors – among others laws and administrative provisions, the facts of the case, form books, notary offices, and the recipient of the document – which determine the content, the specific structure and the language of notarial documents. In addition to the basic parameters of translation, translators should know and tackle the common features and the differences between the notarial documents of the countries concerned in order to produce a professional translation. This paper examines the most important common features and differences between Italian and German real estate sales contracts and presents the implications for translations from Italian into German against the background of the basic parameters of translation.